Expanding the Evidence Base in Criminology and Criminal Justice: Barriers and Opportunities to Bridging Research and Practice. (24th May 2018) - Rodriguez, Nancy
Abstract: Establishing a fair and equitable justice system through criminal justice reform has been a central element of the national conversation on the administration of justice. Issues like the relationship between police departments and communities, mass incarceration, gun violence, and immigrations are at the forefront of U.S. policy and practice. In the current era of reform, there is a legitimate need for research and guidance on how best to advance the justice system and create sustainable reform. In this essay, I explain how my research in the areas of juvenile justice and the impact of mass incarceration on children and families has led to social change. I also draw from my experience as chief scientist within the Department of Justice to share observations about the role of science in informing policy and offer suggestions for improving how researchers can be more effective in the translation of crime and justice research.